Analysis of the influence of profitability, company size, company age, and underwriter's reputation on the underpricing of stocks during the IPO on IDX 2010–2020 period (Asian Journal of Economics and Business Management, 2023)
The capital market is one of the most important means for the business world as a source of capital and a place for investment for the community. Research on the variables influencing underpricing still needs to produce different findings and consistent research results. Investors value companies that have been established for a long time better than experience and stand the test in the business world so that they have a low level of risk. The underwriter's reputation influences the initial share price and has special expertise in corporate securities. This study aims to see the effect of profitability, company size and age, as well as the reputation of the underwriter on stock underpricing at the time of IPO. The method used is the method of regression analysis to see the effect of the independent variables on the dependent variable. The results of this study indicate that the underwriter's profitability and reputation influence the underpricing conditions at the time of the IPO. Public company should pay attention to the size of the company and the underwriter's reputation since these two things affect how much the stock is underpriced and for the investors who want to buy IPOs, it is expected to consider the size of the company and the reputation of the underwriter.